2021
DOI: 10.1016/j.ymthe.2021.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A single dose of self-transcribing and replicating RNA-based SARS-CoV-2 vaccine produces protective adaptive immunity in mice

Abstract: A self-transcribing and replicating RNA (STARR)-based vaccine (LUNAR-COV19) has been developed to prevent SARS-CoV-2 infection. The vaccine encodes an alphavirus-based replicon and the SARS-CoV-2 full-length spike glycoprotein. Translation of the replicon produces a replicase complex that amplifies and prolongs SARS-CoV-2 spike glycoprotein expression. A single prime vaccination in mice led to robust antibody responses, with neutralizing antibody titers increasing up to day 60. Activation of cell-mediated immu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 45 publications
1
107
1
5
Order By: Relevance
“…Other COVID-19 vaccines based on lipid nanoparticle–mRNA formulations are also under evaluation in different clinical phases (Table 1 ). In preclinical studies, some vaccine candidates showed protective effects by delivering self-amplifying RNA encoding the spike protein 40 , 186 , 187 (Box 2 ), a cocktail of mRNAs encoding three viral proteins 74 , modified mRNA encoding the receptor-binding domain 188 or spike mRNA with engineered untranslated regions 107 .
Fig.
…”
Section: Preclinical Studies and Clinical Trialsmentioning
confidence: 99%
“…Other COVID-19 vaccines based on lipid nanoparticle–mRNA formulations are also under evaluation in different clinical phases (Table 1 ). In preclinical studies, some vaccine candidates showed protective effects by delivering self-amplifying RNA encoding the spike protein 40 , 186 , 187 (Box 2 ), a cocktail of mRNAs encoding three viral proteins 74 , modified mRNA encoding the receptor-binding domain 188 or spike mRNA with engineered untranslated regions 107 .
Fig.
…”
Section: Preclinical Studies and Clinical Trialsmentioning
confidence: 99%
“…The company Vaxart has developed a vaccine that uses a nrVV adenovirus type-5 (Ad5), that encodes the complete S glycoprotein as it is expressed by the original SARS-CoV-2, preserving all the components of the S1 and S2 subunits (64). Similarly, the company Arcturus Therapeutics has used a complete S glycoprotein without modifications, however, they have opted for technologies of a self-replicating mRNA ready for translation (65). Other companies such as AstraZeneca and CanSino Biologics have developed nrVV such as AZD1222 and Ad5-nCOV.…”
Section: Full-length S Glycoprotein Vaccinesmentioning
confidence: 99%
“…It encodes the full-length prefusion spike protein. In transgenic mice expressing human angiotensin-converting enzyme 2, doses of 2 µg and 10 µg produced strong T cell responses, high IgG titres and protected mice from SARS-CoV-2 infection 137 . Although the ARCT-021 dose is higher than the LNP-nCoVsaRNA dose, no booster is required, ensuring that recipients are fully vaccinated after a single injection.…”
Section: Progress With Mrna Vaccines For Infectious Diseasesmentioning
confidence: 99%